Securing social media in the enterprise - Dalziel, Henry (Syngress, 2015)
Securing Social Media in the Enterprise is a concise overview of the security threats posed by the use of social media sites and apps in enterprise network environments. Social media sites and apps are now a ubiquitous presence within enterprise systems and networks, and are vulnerable to a wide range of digital systems attacks. This brief volume provides security professionals and network systems administrators a much-needed dive into the most current threats, detection techniques, and defenses for these attacks, and provides a roadmap for best practices to secure and manage social media within the enterprise